„Mahgar“ Literature - Duraković, Esad (Prilozi za orijentalnu filologiju, 2017)
Mahgar literature (the literature of Arab immigrants in the '(J.S.A.), was written mostly between the two World Wars, is an indispensable phenomenon in the study of modern Arabic literature. Written in a crucial period of the development of Arabic literature, it was to a certain extent marked by the time in which it was written, as well as by the influence of Western literature and culture. The mahgar writers were Arab Christians, who emigrated to the U .S.A. from the Lebanon, Syria, and Palestine and founded there a well-known movement that substantially enriched Arabic. Literary tradition. At the time prior to the emigration, these Arab countries had been exposed to powerful Euro-American and Russian influence. The initial interest of. these countries in the Middle East had been motivated by the spread of Christianity. That was the reason why numerous religious missions founded churches and churchboarding schools, where religious and secular subjects were studied. Such education was accompanied by the intensive development of printing and publishing activity in Arabic. Owing to the intensive activity of French, American and Russian missionaries, the above mentioned countries of the ·Near East had become genuine centres of cultural revival. The missionary instituions produced a series of Arab intellectuals who spread the spirit of revival not only in their own countries, but throughout the Arab East, creating a climate which was to enable the generations that fqllowed immediately to realize great achievements in the field of the humanities, creative literature, and literary theory. This generation includes also the mahgar writers, who were well-acquainted with their own literary tradition, but who also knew European and American literature. Being educated emigrants, they gained knowledge in America of certain fundamental differences between). the Oriental and Western mentality, and they most often .observed them through the different prevalence of imagination and ratio, which affected their understanding of art very greatly. The homogenous group of Arab emigrants, drawn closer together by the feeling pf dislocation in a foreign environment, and with their similar attitt1de to art, formed the literary association Al-Rabita al-qalamiyya in New York City in 1920, which very strongly influenced literature in the Arab countries in the course of its 10-year long activity. Two members of the association became especially prominent - Mihail Nuayma and Ghibran Khalil Ghibran who influenced other members of the association a great deal.